KONFLIK PEMBEBASAN LAHAN DALAM RENCANA PEMBANGUNAN WADUK LAMBO DI DESA RENDUBUTOWE, KABUPATEN NAGEKEO, NUSA TENGGARA TIMUR - Gani, Aleksander Rodu; Noak, Piers Andreas; Pramana, Gede Indra (Jurnal Nawala Politika; Vol 1 No 2 (2022): Jurnal Ilmu Politik, 2022)
hisstudyaimstodeterminetheconflictofcommunityresistancetolandacquisitionagainst the construction of reservoirs in the village of Rendubutowe. This study uses qualitative research methods using a qualitative descriptive approach, data collection using observation techniques, interviews and document studies of informants in this study, namely village heads, traditional shops, community shops and youth shops, natives of Rendubutowe village. The results of this study indicate that the people of the village of rendubutowe reject the location of the lambo reservoir construction because the location is a place for the community to meet their daily needs. In this location there are agricultural gardens, traditional ceremonial lands, livestock fields, ancestral graves, and there are some houses of residents of Malpoma Hamlet, Rendubutowe Village. Until now, conflict resolution has not found a common ground between the community and the government because the community still refuses to build the Lambo reservoir. Keyword: Land Acquisition Conflict, Lambo Reservoir Construction, Counflict Theory